Knowledge transfer: what drug information would specialist doctors need to support their clinical practice? Results of a survey and of three focus groups in Italy. Issue 1 (December 2016) - Formoso, Giulio; Rizzini, Paolo; Bassi, Maurizio; Bonfanti, Paolo; Rizzardini, Giuliano; Campomori, Annalisa; Mosconi, Paola
Abstract Background The wide offer of information on pharmaceuticals does not often fulfill physicians' needs: problems of relevance, access, quality and applicability are widely recognized, and doctors often rely on their own experience and expert opinions rather than on available evidence. A quali-quantitative research was carried out in Italy to provide an overview on information seeking behavior and information needs of doctors, in particular of infectious disease specialists, and to suggest an action plan for improving relevance, quality and usability of scientific information. Methods We did a quantitative survey and three focus groups. Two hundred infectious disease specialists answered a 24-item questionnaire aimed at investigating features of scientific information they receive and their ratings about its completeness, quality and usability. Subsequent focus groups, each involving eight specialists, investigated their opinions on information sources and materials, and their suggestions on how these could better support their information needs. Results The quantitative survey indicated doctors' appreciation of traditional channels (especially drug representatives) and information materials (brochures), but also their attitude to autonomous search of information and their wish to have more digital channels available. Focus groups provided more depth and, not surprisingly, revealed that physicians consider critical to get complete, comparative and specific information quickly, but also that they would like to discuss their doubts with expert colleagues. Quite strikingly, limited concerns were expressed on information validity, potential biases and conflicts of interests, as scientific validity seems to be related to the perceived authoritativeness of information sources rather than to the availability of a transparent evaluation framework. Although this research investigated views of infectious disease specialists, we believe that their opinions and perceived needs should not substantially differ from those of other clinicians, either in primary or in secondary care. Conclusions In participants' view, the ideal information framework should provide quick and tailored answers through available evidence and favor the exchange of information between practitioners and trusted experts. The general consensus existing within the scientific and medical community on the need for integrating available evidence and experience is confirmed, although the issues of information validity and conflicts of interests seem definitely overlooked.